REPRESENTATION AND SYMBOLISM OF POWER AND SEXUALITY IN JAMU (UTAMI, 2002) - Gerardus Majella Adhyanggono (Universitas 17 Agustus 1945 Semarang, 2020)
In the first decade following reformasi, three main factors fostered the revival and re-signification of documentary film in Indonesia. First, there was resistance to the New Order’s repressive paradigm of censorship which was still imposed, particularly on issues such as sexuality, religion, and ethnicity. Second, there arose wider freedom for individuals to express their creativity due to the zeitgeist. Third, there was a coherence between the spirit of ‘make-your-own-film’ and the increasing popularity of the digital camera to produce independent films. Ayu Utami’s Jamu (2002) provides a subtle and yet excellent example of a documentary film from this period. It is a documentary that might have never had the opportunity to be made in the New Order regime. The film, set in Jakarta, represents the power of jamu - traditional herbal medicine - which pertains to sexuality and its myth. Using an unconventional expository mode, this film explores jamu as a socio-cultural artifact that forces issues relating to power and sexuality to be brought out into the open. I contend that the representation and symbolism of power and sexuality in the film is predicated on challenging the prevailing view that Indonesia is a moralized society as once constructed by the New Order regime. Therefore, the effect of Jamu can be perceived as twofold: a celebration of freedom of expression and the creative resistance to a hegemonic view of sexuality. My analysis is designed from a semiotic and cultural approach, concerning Roland Barthes’ photographic paradox, Michel Foucault’s power/knowledge, Jeffrey Weeks’s inclusive sexuality, as well as Robert Segal’s and Laurie Honko’s concepts of myth. Keywords: jamu, power, sexuality, and myth